2012
DOI: 10.1186/1447-056x-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication behaviors among Japanese consumers: sex, age, and SES differences and caregivers’ attitudes toward their children’s health management

Abstract: BackgroundSince 2009, when the revised Pharmaceutical Affairs Act was enacted in Japan, self-medication practices have increased. Because the concept of self-medication was recently introduced in Japan, few studies exist on this topic. Therefore, it is necessary to explore how self-medication is practiced. This study examined Japanese consumers’ self-medication practices and attitudes toward over-the-counter (OTC) medicines based on their sex, age, and socioeconomic status (SES).MethodsThe participants were 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 13 publications
2
33
0
1
Order By: Relevance
“…Findings of my study agree with a study in Tanzania by (Monjeza et al,2013).These findings differ with studies elsewhere in which the respondents have a negative attitude towards self-medication. This negative attitude is in harmony with studies in Egypt by (Ezz, 2011) and in Japan by (Aoyama et al, 2012). Studies by Mansour (2015) revealed that more than half of the respondents (60%) were neutral.…”
Section: Discussionsupporting
confidence: 83%
“…Findings of my study agree with a study in Tanzania by (Monjeza et al,2013).These findings differ with studies elsewhere in which the respondents have a negative attitude towards self-medication. This negative attitude is in harmony with studies in Egypt by (Ezz, 2011) and in Japan by (Aoyama et al, 2012). Studies by Mansour (2015) revealed that more than half of the respondents (60%) were neutral.…”
Section: Discussionsupporting
confidence: 83%
“…These results are consistent with another study in Saudi Arabia reported that 53.8% of the parents practiced self-medication in their children [29].This proportions consistent with the global variation of prevalence of self-medication which has been reported by various studies to range between 30-70% [30]. The reasons for such huge global variation many be numerous including different methods used for collecting information, availability of free medical care for children in the public sector hospitals in some countries [31]. Also cultural, social and educational factors have been shown to affect self-medication [29].…”
Section: Discussion:-supporting
confidence: 89%
“…These results differed with study from UK found that parents were generally unaware of potential side effects of OTC medicines because they believed that "over-the-counter medicines are not strong and were unlikely to harm their child," [34]. And study from Japan reported little awareness about adverse effects of non-prescription medicines among participants [35].This difference is due to different at sociodemographic indicators in different countries.…”
Section: Discussion:-mentioning
confidence: 73%
“…Cough, flu, vomiting and diarrhoea were also among the common ailments. In other studies, above mentioned conditions were also reported as most common symptoms in children for which parents practiced self-medication [13,29]. Majority of the medicines used by parents were antipyretics, cough and cold preparations, antimicrobials and antiemetics.…”
Section: Discussionmentioning
confidence: 92%